Dietary Salt Reduction, Prevalence of Hypertension and Avoidable Burden of Stroke in Vietnam: Modelling the Health and Economic Impacts - Aminde, Leopold Ndemnge; Phung, Hai N.; Phung, Dung; Cobiac, Linda J.; Veerman, J. Lennert (Frontiers in Public Health, 2021)
Dietary salt reduction has been recommended as a cost-effective population-wide strategy to prevent cardiovascular disease. The health and economic impact of salt consumption on the future burden of stroke in Vietnam is not known. Objective: To estimate the avoidable incidence of and deaths from stroke, as well as the healthy life years and healthcare costs that could be gained from reducing salt consumption in Vietnam. Methods: This was a macrosimulation health and economic impact assessment study. Data on blood pressure, salt consumption and stroke epidemiology were obtained from the Vietnam 2015 STEPS survey and the Global Burden of Disease study. A proportional multi-cohort multistate lifetable Markov model was used to estimate the impact of achieving the Vietnam national salt targets of 8 g/day by 2025 and 7 g/day by 2030, and to the 5 g/day WHO recommendation by 2030. Probabilistic sensitivity analysis was conducted to quantify the uncertainty in our projections. Results: If the 8 g/day, 7 g/day, and 5 g/day targets were achieved, the prevalence of hypertension could reduce by 1.2% (95% uncertainty interval [UI]: 0.5 to 2.3), 2.0% (95% UI: 0.8 to 3.6), and 3.5% (95% UI: 1.5 to 6.3), respectively. This would translate, respectively, to over 80,000, 180,000, and 257,000 incident strokes and over 18,000, 55,000, and 73,000 stroke deaths averted. By 2025, over 56,554 stroke-related health-adjusted life years (HALYs) could be gained while saving over US 42.6 million in stroke healthcare costs. By 2030, about 206,030 HALYs (for 7 g/day target) and 262,170 HALYs (for 5 g/day target) could be gained while saving over US 88.1 million and US 122.3 million in stroke healthcare costs respectively. Conclusion: Achieving the national salt reduction targets could result in substantial population health and economic benefits. Estimated gains were larger if the WHO salt targets were attained and if changes can be sustained over the longer term. Future work should consider the equity impacts of specific salt reduction programs.